Teknologi Solar Panel untuk Produksi Cendol Sagu Kering (Celsring) di Bagan Melibur - Neni Hermita; Zetra Hainul Putra; Mahmud Alpusari; Gustimal Witri; Eva Astuti Mulyani; Intan Kartika Sari; Naila Fauza; Jesi Alexander Alim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The Meranti Archipelago is the largest producer and exporter of sago in Indonesia. However, in some areas, sago processing sites have not developed optimally, especially in Bagan Melibur Village. Based on this, the research team from the University of Riau carried out community service activities in Bagan Melibur Village, Merbau District, Meranti Islands, Riau on June 25 – July 1, 2021. In this activity, the research team collaborated with MSMEs BAS (Bagan Melibur Amanah Sejahtera) ) and the local community to build a drying house with UV plastic coating that can be used to dry sago cendol food products so that they can be processed into dry food which is expected to optimize the production and marketing of processed sago. Solar radiation that is absorbed directly by UV plastic functions as a conductor and retainer of heat so that the temperature in a place or room is maintained. The achievement of the results obtained in the form of a drying house with solar power that can be used at any time and in cloudy or rainy weather conditions. With this, of course, the production of dry sago cendol can last longer and can be marketed outside the Bagan Melibur area.